Analisis Kesesuaian Kawasan Wisata Pantai Cempae Kecamatan Soreang Kota Parepare - _, Zul Hamizan; Danial, Danial; Asmidar, Asmidar (Program Studi Ilmu Kelautan Fakuktas Ilmu Perikanan dan Kelautan Universitas Muslim Indonesia, 2025)
Beach tourism is a visit made by a person or group of people to enjoy the beauty of the sea and has the aim of doing special activities such as swimming and or just sunbathing on the beach. The purpose of this study is to determine the level of suitability of the Cempae Beach tourist area, Soreang District. This study was conducted in March - April located at Cempae Beach, Soreang District, Parepare City. The method used in this study is land suitability data collection using 10 suitability matrices from Yulianda 2019 with direct observation methods measuring beach type parameters, beach width, water bottom material, water depth, water clarity, current speed, beach slope, coastal land cover, dangerous biota and fresh water availability. The results of the study of the suitability analysis of Cempae Beach tourist land, Soreang District, Parepare City are classified as suitable (S2) with an IKW value of station 1 of 70.67% (S2), the Tourism suitability Index value at station 2 with a figure of 67.00% (2) and for the suitability value of station 3 with a figure of 59.00% (S3). The results of the study show that the level of suitability of Cempae Beach tourism is included in the Suitable category (S2) with an average value of 65.56%, of the 50 respondents who agreed, 65.62% were in the